2003
DOI: 10.1002/adma.200304846
|View full text |Cite
|
Sign up to set email alerts
|

Metal Transfer Printing and Its Application in Organic Field‐Effect Transistor Fabrication

Abstract: is concerned, the present finding bears essential implications for applying the superplastic forming of ceramics into a costeffective industrial production of complex shaped silicon nitride-based components, and for production of other polycrystalline materials that are sintered to full density via a liquid-phase sintering process. ExperimentalThe starting powders were Si 3 N 4 (Ube, SN-E10), AlN (HC Starck, Grade C), Al 2 O 3 , Y 2 O 3 , and Yb 2 O 3 (Johnson Matthey Chemicals Ltd.). When calculating the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 23 publications
0
60
0
Order By: Relevance
“…Recently, a series of technologies have been developed based on microcontact printing (mCP), such as decal transfer microlithography [96], nanotransfer printing [94] and metal transfer printing [97,98]. Jeon et al [99] found that the surface coverage of octadecyltrichlorosilane (OTS) was augmented by prolongation of contact time.…”
Section: Microcontact Printingmentioning
confidence: 99%
“…Recently, a series of technologies have been developed based on microcontact printing (mCP), such as decal transfer microlithography [96], nanotransfer printing [94] and metal transfer printing [97,98]. Jeon et al [99] found that the surface coverage of octadecyltrichlorosilane (OTS) was augmented by prolongation of contact time.…”
Section: Microcontact Printingmentioning
confidence: 99%
“…In order to address the current problems of microfabrication on flexible substrate, many alternative approaches to conventional photolithography-based process have been introduced by a number of researchers. These include microcontact printing (lCP) combined with metal etching, [10] electroless plating, [11] electropolymerization, [12] and direct metal layer transfer [13] for the microscale metal patterning on flexible substrates. Stencil lithography [14] was mainly applied for dielectric layer patterning on polymer substrates for the formation of electrical capacitors [15,16] due to its limited resolution.…”
mentioning
confidence: 99%
“…[ 41] Here we found that metal transference could also be initiated at room temperature under pressure with a slightly longer printing time. Forty-nm Au was thermally evaporated on structured stamps.…”
Section: Printing Metal Structures On a Homogeneous Nanoparticle/ Polmentioning
confidence: 95%